Seismic performance of self-consolidating concrete bridge columns. (1st April 2018) - Ghadban, Ahmad A.; Wehbe, Nadim I.; Pauly, Todd
Highlights: The strain at strength and ultimate strain of SCC are higher than those of CC. The elastic modulus of SCC is lower than that of CC. The displacement ductility of CC columns is higher than that of SCC columns. Energy absorbed before failure by CC columns is higher than that of SCC columns. The seismic performance of SCC columns is adequate and is comparable to CC columns. Abstract: The high amount of confining lateral steel required by seismic design provisions for rectangular bridge columns can cause steel congestion which may hinder the placement of conventional concrete (CC). Self-consolidating concrete (SCC) eliminates or reduces concrete placement and consolidation issues; however, there is limited data on the seismic performance of SCC bridge columns. This study encompassed experimental investigations to assess the stress-strain relationships of SCC mixes and the seismic performance of rectangular SCC bridge columns. SCC and CC rectangular columns were tested. Experimental results showed that the strain at strength and the ultimate strain of SCC are higher than those of CC, while concrete ductility and the elastic modulus of SCC are lower than those of CC. Experimental results of the column tests showed that the use of SCC reduces displacement ductility and energy dissipation but increases drift ratio at failure. The SCC column performance under inelastic cyclic lateral loading was found to be satisfactory and comparable to that of CC columns.